2020
DOI: 10.1136/jitc-2019-000367
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and biomarker analysis of nivolumab plus gemcitabine and cisplatin in patients with unresectable or metastatic biliary tract cancers: results from a phase II study

Abstract: BackgroundThe prognosis of patients with unresectable or metastatic biliary tract cancer (BTC) is unacceptably low. This study aimed to determine the efficacy, safety and predictive biomarkers of the immune checkpoint inhibitor nivolumab in combination with chemotherapy in advanced BTCs.MethodsIn this open-label, single-arm, phase II trial, a chemotherapy and immunotherapy combination consisting of gemcitabine 1000 mg/m2, cisplatin 75 mg/m2and nivolumab 3 mg/kg was administered every 3 weeks for up to six cycl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 41 publications
3
83
0
Order By: Relevance
“…15 Recently, the whole-exome sequencing in one phase II study shown that TMB, tumor neoantigen burden (TNB), and the mutation of RYR2, MUC4, and APOB could predict the efficacy of nivolumab plus gemcitabine and cisplatin for BTCs. 16 However, no other extensive analyses of genomic correlates of immunotherapy response have been carried out in BTCs.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, the whole-exome sequencing in one phase II study shown that TMB, tumor neoantigen burden (TNB), and the mutation of RYR2, MUC4, and APOB could predict the efficacy of nivolumab plus gemcitabine and cisplatin for BTCs. 16 However, no other extensive analyses of genomic correlates of immunotherapy response have been carried out in BTCs.…”
Section: Introductionmentioning
confidence: 99%
“…No significant survival benefit was observed for this combination when compared with other combinations in clinical trials ( 56 58 ). However, it has promising efficacy and a manageable safety profile in patients with advanced CCA ( 56 ). Patients with iCCA with high insertion-deletion ratios can also benefit from treatment with this combination ( 59 ).…”
Section: Combined Therapymentioning
confidence: 73%
“…Of the 6 patients who were resistant to gemcitabine-based or cisplatin-based chemotherapy, one CR and one PR were achieved. This result indicates that, as a PD-1 inhibitor, nivolumab is able to resensitize BTC to gemcitabine and cisplatin chemotherapy ( 56 ). No significant survival benefit was observed for this combination when compared with other combinations in clinical trials ( 56 58 ).…”
Section: Combined Therapymentioning
confidence: 95%
See 2 more Smart Citations